2015
DOI: 10.1002/jhm.2388
|View full text |Cite
|
Sign up to set email alerts
|

Improving and sustaining a reduction in iatrogenic pneumothorax through a multifaceted quality‐improvement approach

Abstract: BACKGROUND The Agency for Healthcare Research and Quality has adopted iatrogenic pneumothorax (IAP) as a Patient Safety Indicator. In 2006, in response to a low performance ranking for IAP rate from the University Healthsystem Consortium (UHC), the authors established a multidisciplinary team to reduce our institution’s IAP rate. Root-cause analysis found that subclavian insertion of central venous catheterization (CVC) was the most common procedure associated with IAP OBJECTIVE Our short-term goal was a 50%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…Simulation-based educational initiatives for CVC training improve learner performance and confidence, and have led to improvement in some patient outcomes. 8 , 9 , 12 14 Simulation is among the most frequently studied educational modes for procedural instruction in invasive bedside procedures. 15 …”
Section: Introductionmentioning
confidence: 99%
“…Simulation-based educational initiatives for CVC training improve learner performance and confidence, and have led to improvement in some patient outcomes. 8 , 9 , 12 14 Simulation is among the most frequently studied educational modes for procedural instruction in invasive bedside procedures. 15 …”
Section: Introductionmentioning
confidence: 99%
“…Bu durum hastanede kalış süresini de etkilemektedir. Hastanede kalış süresinin kısalması ile morbiditemortalite oranları azalmakta ve hasta maliyeti de düşmektedir (18)(19)(20) .…”
Section: Discussionunclassified
“… 9 Three prospective studies reported a sensitivity of 75% and a specificity of 100% for assessing inappropriate catheter positioning compared to bedside chest radiography. 10 , 11 , 12 The second method, based on the rapid flush of a saline−air mixture through the inserted catheter, is more sensitive. 4 , 5 Correct catheter positioning is detected as the appearance within 2 seconds of multiple micobubbles in the right atrium.…”
Section: Discussionmentioning
confidence: 99%